Paradoxical cerebral embolism due to transiently patent foramen ovale as a complication of massive pulmonary thromboembolism: Case Report - Flores Palacios, Rodrigo Jesús (2024)
Paradoxical cerebral embolism always requires the presence of a patent foramen ovale (PFO); in our case, this event occurred due to a transient phenomenon, which was the acute overload of the right heart chambers and the opening of the PFO due to increased pressures as a consequence of massive pulmonary thromboembolism. After undergoing arthroscopy, this patient presented with visual field loss and progressive dyspnea, ultimately leading to mechanical ventilation and severe obstructive shock. An angiotomography was performed, revealing an obstructive thrombus in the right pulmonary artery. The patient successfully underwent thrombolysis, and she was discharged from the intensive care unit after 45 days. Ultimately, protein C deficiency was diagnosed, and permanent anticoagulation was initiated. The presence of motor deficit and dyspnea in a post-knee surgery patient should raise suspicion of pulmonary thromboembolism. Thrombolysis remains the treatment of choice, and it should be timely prescribed and performed.